Analisis Kesalahan Menyusun Kalimat Tanya Bahasa Jerman - Fajri, Surya Nurul; R, Mantasiah; Saud, Syukur (Universitas Negeri Makassar, 2025)
Abstract. This research is a qualitative descriptive study aimed at identifying the forms of errors in constructing German interrogative sentences and the factors that cause students of class XI IPS 7 at SMAN 15 Makassar to make these errors. The data in this study consists of the results of a test on constructing German interrogative sentences and a questionnaire on the factors contributing to errors in forming such sentences. The data sources were obtained from the German interrogative sentence construction test completed by 35 students of class XI IPS 7 at SMAN 15 Makassar. These students were selected based on an interview with the German teacher, who stated that many students in this class were prone to making errors in constructing interrogative sentences. Based on the research instruments and data collection techniques, this study used tests and questionnaires to obtain research data. The results of the error analysis in constructing German interrogative sentences revealed three (3) forms of errors, totaling 411 instances (65.23%). These errors consist of verb conjugation errors (200 instances, 48.6%), subject placement errors (191 instances, 46.4%), and interrogative word placement errors (20 instances, 5.0%). Errors in constructing German interrogative sentences among all students were most commonly found in questions using the interrogative word was, with a total of 81 errors (19.71%). The overall percentage of errors in constructing German interrogative sentences among class XI IPS 7 students at SMAN 15 Makassar was 65.23%, which falls into the